Internalization and Trafficking of Cell Surface Proteoglycans and Proteoglycan-Binding Ligands - Payne, Christine K. (2007)
Using multi-color live cell imaging in combination with biochemical assays we have investigated an endocytic pathway mediated by cell surface proteoglycans, primary receptors for many cationic ligands. We have characterized this pathway for a variety of proteoglycan-binding ligands including cationic polymers, lipids, and polypeptides. Following clathrin- and caveolin-independent, but flotillin- and dynamin-dependent internalization, proteoglycan-bound ligands associate with flotillin-1-positive vesicles and are efficiently trafficked to late endosomes. The route to late endosomes differs considerably from that following clathrin-mediated endocytosis. The proteoglycan-dependent pathway to late endosomes does not require microtubule-dependent transport or PI(3)K-dependent sorting from early endosomes. The pathway taken by these ligands is identical to that taken by an antibody against heparan sulfate proteoglycans, suggesting this mechanism may be used generally by cell surface proteoglycans and proteoglycan-binding ligands without secondary receptors.